Insight observation into rapid discoloration of batik textile effluent by in situ formations of zero valent iron - Mohd Shaiful Sajab; Nur Nadia Nazirah Ismail; Jude Santanaraj; Abdul Wahab Mohammad; Hassimi Abu Hassan; Chia, Chin Hua; Sarani Zakaria; An'amt Mohamed Noor (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aimed to investigate the discoloration of textile effluent from batik industrial wastewater by Fenton oxidation process using Fe(II), Fe(III) and in situ formation of zero valent iron (Fe(0)). The controlled parameters indicate the Fenton oxidation reaction is ideal on effluent at pH5, concentration colour of 4005 mg/L Pt-Co units using 0.5 mg/mL of catalyst dosage to meet the regulation for Malaysian quality water standard. The optimization of Fe(0) precursors, Fe(II) shows a higher discoloration efficiency in comparison with Fe(III). The synthesized particles of Fe(0) shows a nano spherical structure in the diameter range of 20-70 nm, aggregated and into a chain-like formation. Subsequently, the performance of Fe(0) was improved up to 97% discoloration in comparison with 89% discoloration by Fe(II). Whereas, the in situ formation of Fe(0) in batik effluent shows a complete discoloration ascribable to higher reactivity than partially oxidized of synthesized ex situ Fe(0). On top of that, in situ Fe(0) performed at the expeditious reaction in less than five min. Additionally, the regeneration of Fe(0), Fe(II) and Fe(III) show a potential of catalyst recyclability up to three cycles of Fenton oxidation but with a tolerable reduction to 62.1% of effluent discoloration.